Molecular Dynamic Simulation of Amine-CO2 Absorption Process - Noorlisa, Harun; E. E., Masiren (Informatics Publishing Limited, 2017)
Objectives: Modelling and simulation of amine absorption process for CO2 removal at macro-scale is well established. This study used to investigate the amine-CO2 absorption process at molecular level using Molecular Dynamic (MD) simula¬tion. Methods/Statistical Analysis: Analysis on different types of amine and blended amines for absorption process was conducted in this study. COMPASS and Ewald models used for force field and summation method calculation, respectively. Findings: The results shows MEA solvent was the highest tendency (39.70%) to interact with CO2 compared to DEA and MDEA because can directly react with CO2 and easily form carbamate ions. Due to the lack of –HN bond in MDEA, it was determined to be less reactive and suggested to be blended with other reactive amines. Blended MDEA/AMP (33.50%) and MDEA/PZ (23.80%) improved the efficiency of MDEA in CO2 absorption process. The addition of AMP and PZ assisted MDEA to have intermolecular interaction with CO2. Application/Improvements: Research on molecular modelling of amine absorption process for CO2 capture was proposed in this study to give insight about this process at molecular level and to analyse the intermolecular interaction between CO2 and amine solution.